Does Government Fragmentation and Fiscal Decentralization Constrain Leviathan? New evidence from experience in Indonesia - Zulyanto, Aan; Badriah, Lilis Siti (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2024)
Since the reform era 1999, Indonesia has made a regional proliferation policy and widespread fiscal decentralization policy. Based on the Leviathan hypothesis, the two policies should create a competitive climate and increase the efficiency of government spending. This study aims to analyze the Leviathan hypothesis in Indonesia's regional proliferation policy and fiscal decentralization. The study uses panel data regression from 32 provinces during the 2002-2020 period. The study finds that the Leviathan hypothesis does not apply to Indonesia's regional proliferation and fiscal decentralization policies. Fiscal decentralization and government fragmentation apparently cannot constrain local government size. They have a significant positive effect on increasing it. The results of this study imply that to obtain tangible benefits from regional expansion, a thorough understanding of regional economic potential is needed, as well as the need to improve the quality of human resources to utilize regional potentials optimally.